The forsaken mental health of the Indigenous Peoples - a moral case of outrageous exclusion in Latin America - Maldonado-Bouchard Sioui; Incayawar Mario (BMC, 2009)
Abstract Background Mental health is neglected in most parts of the world. For the Indigenous Peoples of Latin America, the plight is even more severe as there are no specific mental health services designed for them altogether. Given the high importance of mental health for general health, the status quo is unacceptable. Lack of research on the subject of Indigenous Peoples' mental health means that statistics are virtually unavailable. To illustrate their mental health status, one can nonetheless point to the high rates of poverty and extreme poverty in their communities, overcrowded housing, illiteracy, and lack of basic sanitary services such as water, electricity and sewage. At the dawn of the XXI century, they remain poor, powerless, and voiceless. They remain severely excluded from mainstream society despite being the first inhabitants of this continent and being an estimated of 48 million people. This paper comments, specifically, on the limited impact of the Pan American Health Organization's mental health initiative on the Indigenous Peoples of Latin America. Discussion The Pan American Health Organization's sponsored workshop "Programas y Servicios de Salud Mental en Communidades Indígenas" [Mental Health Programs and Services for the Indigenous Communities] in the city of Santa Cruz, Bolivia on July16 - 18, 1998, appeared promising. However, eleven years later, no specific mental health program has been designed nor developed for the Indigenous Peoples in Latin America. This paper makes four specific recommendations for improvements in the approach of the Pan American Health Organization: (1) focus activities on what can be done; (2) build partnerships with the Indigenous Peoples; (3) consider traditional healers as essential partners in any mental health effort; and (4) conduct basic research on the mental health status of the Indigenous Peoples prior to the programming of any mental health service. Summary The persistent neglect of the Indigenous Peoples' mental health in Latin America raises serious concerns of moral and human rights violations. Since the Pan American Health Organization' Health of the Indigenous Peoples Initiative 16 years ago, no mental health service designed for them has yet been created.